2010
DOI: 10.1200/jco.2009.25.1835
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin Alfa in Patients With Advanced-Stage Hodgkin's Lymphoma: Results of the Randomized Placebo-Controlled GHSG HD15EPO Trial

Abstract: Epoetin alfa administered at 40,000 U weekly parallel to BEACOPP chemotherapy was safe in patients with advanced-stage HL and reduced the number of RBC transfusions but had no impact on fatigue and other PRO domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Moreover, the drug label and current ASH/ASCO guidelines [28,42] generally recommend not to use ESA in patients with curative intent, although convincing data are lacking that transfusions carry a lower risk in this patient group than ESA. By contrast, several recent prospective randomised trials using ESA with curative intent did not provide evidence of an impact on survival or relapse in patients with Hodgkin's lymphoma [46], aggressive lymphoma [47], cervical cancer [48] and early breast cancer [49]. Furthermore, several studies and 3 meta-analyses [20,21,50] have shown that transfusions rather increase the risk of complications such as cardiovascular disease [23], acute lung injury [19], haemolytic reactions [19], postoperative infection [19,20] and surgical re-intervention [20], as well as the risk of relapse [20,21,24], all-cause [19,20,22,23,24,51] and cancer-related mortality [20], and may induce malignant lymphomas [50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the drug label and current ASH/ASCO guidelines [28,42] generally recommend not to use ESA in patients with curative intent, although convincing data are lacking that transfusions carry a lower risk in this patient group than ESA. By contrast, several recent prospective randomised trials using ESA with curative intent did not provide evidence of an impact on survival or relapse in patients with Hodgkin's lymphoma [46], aggressive lymphoma [47], cervical cancer [48] and early breast cancer [49]. Furthermore, several studies and 3 meta-analyses [20,21,50] have shown that transfusions rather increase the risk of complications such as cardiovascular disease [23], acute lung injury [19], haemolytic reactions [19], postoperative infection [19,20] and surgical re-intervention [20], as well as the risk of relapse [20,21,24], all-cause [19,20,22,23,24,51] and cancer-related mortality [20], and may induce malignant lymphomas [50].…”
Section: Discussionmentioning
confidence: 99%
“…Positive findings from observational studies (Glaspy et al , 1997; Demetri et al , 1998; Gabrilove et al , 2001; Quirt et al , 2001; Cella et al , 2003) and clinical trials (Littlewood et al , 2001; Fallowfield et al , 2002; Chang et al , 2005; Wilkinson et al , 2006) have not been confirmed in more recent RCTs (Smith et al , 2008; Hoskin et al , 2009; Engert et al , 2010; Fujisaka et al , 2011; Nitz et al , 2011). Previous meta-analyses have demonstrated that ESAs effectively reduce fatigue-related symptoms in cancer patients (Minton et al , 2008, 2010; Tonelli et al , 2009).…”
mentioning
confidence: 94%
“…In addition, American guidelines encourage a risk benefit evaluation prior to the use of ESAs, which appears difficult on the basis of the individual patient, in particular given the lack of reliable predictors of response. However, as there is good evidence that the risks associated with the use of ESAs according to current guidelines are low [30][31][32][33]47,48 , minor benefits may already outweigh those. Interestingly, we found the most striking differences in QoL improvements using the response criterion of any Hb increase.…”
Section: Discussionmentioning
confidence: 83%
“…As a consequence, the ESA drug label has changed and official treatment guidelines have been revised several times [24][25][26][27][28][29] . However, evidence of such a risk in daily practice is lacking, and recent safety trials have provided data suggesting that use of ESAs according to guidelines is not associated with any decrease of survival in patients with Hodgkin's lymphoma 30 , aggressive lymphoma 31 , cervical cancer 32 , and early breast cancer 33 .…”
Section: Introductionmentioning
confidence: 98%